2018
DOI: 10.1038/s41598-018-29955-w
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid predicts incident metabolic syndrome in the elderly in an analysis of the Brisighella Heart Study

Abstract: Several epidemiological studies report a positive correlation between hyperuricemia and metabolic syndrome (MetS) in adults, which hyperuricemic subjects seem to more easily develop. We aimed to verify if serum uric acid (SUA) concentrations were positively associated with MetS prevalence and middle-term (4-year) incidence in older overall healthy subjects. We also purposed to identify which SUA cut-off values could be functional in MetS diagnosis in addition to the traditionally used parameters. For this reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 29 publications
(29 reference statements)
3
52
1
4
Order By: Relevance
“…Serum uric acid, previously known to have a beneficial effect as an oxygen radical scavenger [21], is now recognized to carry a vital role as the modulator of glucose and lipid metabolism [22], leading to observations that the breach of serum uric acid homeostasis may be associated with cardiovascular risk and all-cause mortality [22][23][24]. Current studies demonstrate the possibility of serum uric acid level as a predictor of incident metabolic syndrome [25] and, when combined with LDL-C, of incident hypertension [26]. However, the independent role of serum uric acid as a novel risk factor and a target for treatment regardless of the clinical history of gout has been a subject of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Serum uric acid, previously known to have a beneficial effect as an oxygen radical scavenger [21], is now recognized to carry a vital role as the modulator of glucose and lipid metabolism [22], leading to observations that the breach of serum uric acid homeostasis may be associated with cardiovascular risk and all-cause mortality [22][23][24]. Current studies demonstrate the possibility of serum uric acid level as a predictor of incident metabolic syndrome [25] and, when combined with LDL-C, of incident hypertension [26]. However, the independent role of serum uric acid as a novel risk factor and a target for treatment regardless of the clinical history of gout has been a subject of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Trained personnel performed laboratory analyses according to standardized methods [15], immediately after centrifugation, to assess TC, HDL-C, TG, Apo-B, apolipoprotein A1 (Apo-A1), fasting plasma glucose (FPG), creatinine, estimated glomerular filtration rate (eGFR) and liver transaminases. LDL-C was obtained by the Friedewald formula.…”
Section: Laboratory Datamentioning
confidence: 99%
“…21,22 In a scientific report by Cicero AF et al, MetS was more frequent for higher SUA concentrations rather than the population's mean in both men and women. 23 Yuan H et al; in their meta-analysis, concluded that higher SUA levels led to an increased risk of MS regardless of the study characteristics, and were consistent with a linear dose-response relationship. In addition, SUA was also a causal factor for the non alcoholic fatty liver disease (NAFLD) risk.…”
Section: Discussionmentioning
confidence: 89%